The impact of continuous assessments in replacing mid-semester examinations for undergraduate pharmacy students at International Islamic University Malaysia - Zin, Che Suraya; Bux, Siti Halimah; Awang, Mohamed (2011)
Background: Continuous assessment and exam are two ways of assessments that many universities around the world are using. At the school (Kulliyyah) of pharmacy, International Islamic University Malaysia, continuous assessment, mid-semester examination and end of semester examination are used as methods of assessment for undergraduate pharmacy students. In a revised academic curriculum, the mid-semester examination was abolished and was replaced by continuous assessments. The implementation of a revised academic curriculum only affected a new cohort of first year students, while pharmacy students at year two, three and four still follow the old curriculum. Among the subjects offered for year one are introduction to pharmacy practice, fundamentals of physiology and physical pharmacy. These subjects are taught over a period of 14 weeks. The methods of continuous assessment include quizzes, small tests, seminars and reports. These types of assessment are conducted throughout the semester and they do not put students under great pressure as in the case of mid and end of semester examination. The overall score of the mid-semester examination or continuous assessments contribute to 40% of the total score at the end of semester examination This study examines the impact of continuous assessments on the overall student academic performance. Setting: School of Pharmacy International Islamic University Malaysia Methods: Two groups of students from different batches were included in this study. The first group consists of 105 students who undertook the mid semester examination under the old academic curriculum. These students are currently in year two. Their academic performance when they were in year one was included in this study. The second group consists of 101 students who undertook the continuous assessment under the revised academic curriculum. At present, this group is in year one. This study compared the academic performance of these two groups of students in the introduction to pharmacy practice course during the end of semester examination. The two groups received same teaching syllabus and same coverage of questions for the end of semester exam. The performance was ranked according to very good (75-100%), good (60-74%), fair (50-59%), poor (45-49%) and very poor (≤ 44%). Result: The findings from this study showed that 17.1% (n=18/105) of students in the group one (mid semester examination) and 23.8% (n=24/101) of students in the group two(continuous assessment) were ranked as very good in their academic performance in the introduction to pharmacy practice subject during end of semester examination. Both groups demonstrated similar proportions of students in the ranking of good result (76.2%, n=80/105, group 1 and n=77/101, group 2). There were 4.8% (n=5/105) of students in group one and none in group two obtained fair achievement in their academic performance. One point nine percent (n=2/105) of students showed poor and none showed very poor academic performance in group one. None of the students obtained poor and very poor ranking in the group two. The comparison between the two groups for very good ranking was not statistically significant (p > 0.05, chi square test)